Staphylococcus aureus-specific TIGIT+ Treg are present in the blood of healthy subjects – a hurdle for vaccination? - Clegg, Jonah; Mnich, Malgorzata E.; Carignano, Alberto; Cova, Giovanni; Tavarini, Simona; Sammicheli, Chiara; Clemente, Bruna; Smith, Megan; Siena, Emilio; Bardelli, Monia; Brazzoli, Michela; Bagnoli, Fabio; et al. (Frontiers in Immunology, 2025)
Staphylococcus aureus poses an enormous burden of morbidity and mortality worldwide. Making an efficacious vaccine has however proven extremely challenging. Due to colonizing interactions, pre-existing S. aureus-specific CD4+ T cells are often found in the human population and yet a detailed characterization of their phenotypes and how they might in turn impact vaccine efficacy are thus far unknown. Using an activation induced marker assay to sort for S. aureus-specific CD4+ T cells in an effector function-independent manner, single cell transcriptomic analysis was conducted. Remarkably, S. aureus-specific CD4+ T cells consisted not only of a broader spectrum of conventional T cells (Tcon) than previously described but also of regulatory T cells (Treg). As compared to polyclonally-activated CD4+ T cells, S. aureus-specific Tcon were enriched for the expression of the Th17-type cytokine genes IL17A, IL22 and IL26, while higher percentages of S. aureus-specific Treg expressed the T Cell Immunoreceptor with Ig and ITIM domains (TIGIT), a pleiotropic immune checkpoint. Notably, the antagonistic anti-TIGIT mAb Tiragolumab increased IL-1β production in response to S. aureus in vitro. Therefore, these results uncover the presence of S. aureus-specific TIGIT+ Treg in the blood of healthy subjects that could blunt responses to vaccination and indicate TIGIT as a potential targetable biomarker to overcome pre-exposure-induced immunosuppression.